Sustainable building design - Wang, Nengmou; Adeli, Hojjat (Journal of Civil Engineering and Management, 2014)
Sustainable building design has become a wide and multidisciplinary research endeavor including mechanical, electrical, electronic, communication, acoustic, architectural, and structural engineering. It involves the participation of owners, contractors, suppliers and building users. There has been a lot of talk about sustainable buildings in the past few years. Most of the published research is concerned with saving energy and water and making the buildings more environmentally friendly by, say, reducing the carbon emissions. In this article, sustainable building design is reviewed from the viewpoint of structural engineering. Different strategies presented in the literature are summarized. Finally, the authors argue that the next big leap in sustainable building design should come from the integration of the smart structure technology including the use of hybrid and semi-active vibration controllers that can result in substantially lighter and more efficient structures.